2020
DOI: 10.1016/j.resinv.2020.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Serum KL-6 level is a useful biomarker for evaluating the severity of coronavirus disease 2019

Abstract: Background Coronavirus disease 2019 (COVID-19) is currently spreading worldwide. This study examined whether serum Krebs von den Lungen-6 (KL-6) level is a useful biomarker for evaluating the severity of COVID-19. Methods We retrospectively examined patients diagnosed with COVID-19 at the Japanese Red Cross Medical Center between February 1, 2020, and May 15, 2020. Patients were divided into four categories based on clinical and radiological findings: mild, moderate, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
61
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(72 citation statements)
references
References 23 publications
8
61
3
Order By: Relevance
“…KL‐6 is mainly produced by damaged or regenerating alveolar type II pneumocytes 39 . Both baseline or peak serum KL‐6 levels were higher in critical and severe COVID‐19 cases than in nonsevere cases 225 . Consistently, another study also demonstrated higher serum concentrations of KL‐6 in severe patients than in nonsevere patients, with a cutoff value of 406.5 U/ml 39 .…”
Section: Laboratory Indicatorsmentioning
confidence: 62%
“…KL‐6 is mainly produced by damaged or regenerating alveolar type II pneumocytes 39 . Both baseline or peak serum KL‐6 levels were higher in critical and severe COVID‐19 cases than in nonsevere cases 225 . Consistently, another study also demonstrated higher serum concentrations of KL‐6 in severe patients than in nonsevere patients, with a cutoff value of 406.5 U/ml 39 .…”
Section: Laboratory Indicatorsmentioning
confidence: 62%
“…On the other hand, the elevated serum KL-6 may be also related to the more severe lung injury occurring in the severe COVID-19 patients. The previous studies have reported that serum KL-6 may be used to evaluate the severity of COVID-19 [14] , [30] . A very recent study also reported that serum KL-6 may be a novel biomarker for accessing COVID-19 severity and predicting the prognosis of lung injury [31] .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that there is a complexity of interactions between coexisting idiopathic pulmonary fibrosis/ILD and COVID-19 disease [6] . Serum KL-6 has been suggested to be a useful biomarker for evaluating the severity of COVID-19, however, the results from another research did not demonstrate that KL-6 can discriminate different ventilatory phenotypes in COVID-19 patients [14] , [15] , [16] . Moreover, pulmonary fibrosis is identified by excessive deposition of extracellular matrix (ECM) proteins, such as fibronectin (Fn) [17] .…”
Section: Introductionmentioning
confidence: 93%
“…Moreover, KL-6 has been also proposed as bioindicator of acute respiratory distress syndrome (ARDS) and infective pneumonia (ref). Since the outbreak of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic, KL-6 has also been proposed as a prognostic marker for this disease [6][7][8][9]. The pathogenesis of COVID-19 (as the lung disease caused by SARS-CoV-2 is defined) is not entirely clear [10], although it is postulated that elevated serum concentrations of proinflammatory cytokines and oxidative…”
Section: Introductionmentioning
confidence: 99%